A kind of UV cationic delayed curing adhesive and its preparation method and application
By using epoxy monomers with different induction periods and suitable cationic photoinitiators in UV cation delay curing glue, the problems of poor curing depth and difficulty in bonding of opaque substrates in non-colored systems are solved, and efficient bonding and curing effects are achieved.
Patent Information
- Application Number
- CN202510081139.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional UV acrylate adhesives have poor curing depth in non-colored systems and cannot effectively bond both sides as opaque substrates.
By selecting epoxy monomers with different induction periods for compounding, and combining with suitable types and proportions of cationic photoinitiators, a UV cation delayed curing glue was developed. The glue has a certain reaction induction period after UV light to ensure that there is no obvious gel curing within a certain period of time. It will be quickly gelled and cured after the induction period to achieve the best curing effect and bonding strength.
Effective bonding and curing of opaque substrates is achieved, the problem of poor curing depth of traditional UV glue systems is solved, and the bonding strength and process flexibility are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electronic and electrical materials, and specifically relates to a UV cationic delayed curing adhesive and a preparation method and application thereof. Background Art
[0002] UV-curing adhesives are widely used in the field of electronics and electrical due to their advantages such as fast curing speed, no solvent, low VOC emissions, energy saving and environmental protection. Traditional UV acrylic adhesives have the advantages of fast curing speed and high bonding strength, but they also require that at least one side of the adhered substrate must be transparent. In colored systems, due to poor light transmittance, light cannot reach deep into the adhesive layer and cannot effectively excite the photoinitiator, thus affecting the curing depth. And the shrinkage rate after curing is high. Although UV-curing epoxy systems can achieve better curing effects through post-curing such as cationic dark reaction or heating curing, they still cannot achieve bonding to substrates that are opaque on both sides. Summary of the invention
[0003] The present invention prepares a UV cationic delayed curing adhesive by compounding epoxy monomers with different induction periods and matching them with appropriate cationic photoinitiator types and proportions. The delayed curing adhesive can be firstly coated on one side of a substrate. After UV irradiation, the existence of the glue reaction induction period can ensure that the glue has no obvious gel curing within a certain period of time, and can meet the requirements of the production bonding process. After the induction period, the glue quickly gels and cures to produce a certain bonding strength, thereby meeting the requirements of substrate bonding and positioning. Subsequently, the best curing effect and bonding strength are achieved through post-curing of the cationic dark reaction.
[0004] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0005] The present invention provides a UV cationic delayed curing adhesive, which comprises the following components in parts by weight:
[0006]
[0007] Preferably, the aliphatic epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and modified epoxy resin; the modified epoxy resin is selected from polyurethane modified epoxy resin or polyether modified epoxy resin.
[0008] Furthermore, the aliphatic epoxy resin is bisphenol A epoxy resin YD-172, and the modified epoxy resin is polyurethane modified epoxy resin EPUM1002 and polyether modified epoxy resin EP4000.
[0009] Preferably, the alicyclic epoxy resin is selected from one or more of bis((3,4-epoxycyclohexyl)methyl)adipate, 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, 4-vinyl-1-cyclohexene diepoxide and 3,4,3',4'-diepoxydicyclohexane.
[0010] Furthermore, the alicyclic epoxy resin is bis((3,4-epoxycyclohexyl)methyl)adipate, which is mainly used to enhance the cationic curing rate of the UV delayed adhesive.
[0011] Preferably, the epoxy toughening agent is selected from epoxidized butadiene or polyurethane toughening agent.
[0012] Furthermore, the epoxy toughening agent is polybutadiene-modified epoxy resin BP3600 and MX-154, which are mainly used to modify the toughness of UV delayed curing adhesive.
[0013] Preferably, the oxetane is selected from one or more of 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-[[(2-ethylhexyl)oxy]methyl]oxetane, 3-ethyl-3-((oxiranylmethoxy)methyl)oxetane and 3,3'-(oxybismethylene)bis(3-ethyl)oxetane.
[0014] Furthermore, the oxetane is 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-[[(2-ethylhexyl)oxy]methyl]oxetane, which is mainly used after UV irradiation to provide a certain curing open time by utilizing its different reaction induction period, and has a faster curing rate after the induction period.
[0015] Preferably, the epoxy diluent is selected from one or more of butyl glycidyl ether, dodecanediol glycidyl ether, 1,4-hexanediol diglycidyl ether and 1,6-hexanediol diglycidyl ether.
[0016] Furthermore, the epoxy diluent is butyl glycidyl ether, dodecanediyl glycidyl ether, 1,4-hexanediol diglycidyl ether, and has a relatively long reaction induction period, and is mainly used in conjunction with oxetane to adjust the curing rate and open time.
[0017] Preferably, the cationic photoinitiator is selected from one or more of 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluorophosphate, (4-octyloxyphenyl)phenyliodonium hexafluoroantimonate, triarylsulfonium salt mixed initiator (6976) and triarylsulfonium salt mixed initiator (6992).
[0018] Furthermore, the cationic photoinitiator is a triarylsulfonium salt mixed initiator (UVI-6976), which is mainly used to generate strong proton acid after UV irradiation to initiate cationic polymerization.
[0019] Preferably, the thermal initiator is dibenzoyl peroxide (BPO).
[0020] Furthermore, the thermal initiator is 30% effective content of dibenzoyl peroxide (BPO), which is mainly used to absorb the heat generated by the curing reaction, shorten the reaction induction period and increase the curing rate after the induction period.
[0021] Preferably, the silicon dioxide is R202 or TS720.
[0022] Furthermore, the silicon dioxide is TS720.
[0023] The present invention also provides a method for preparing the above-mentioned UV cationic delayed curing adhesive, comprising the following steps:
[0024] (1) mixing 20-30 parts of aliphatic epoxy resin, 5-10 parts of alicyclic epoxy resin, 15-20 parts of epoxy toughening agent, 20-30 parts of oxetane, and 5-10 parts of epoxy diluent by weight to obtain a mixture A;
[0025] (2) further mixing the mixture A with 2-5 parts of a cationic photoinitiator and 2-5 parts of silicon dioxide to obtain a mixture B;
[0026] (3) Cooling the mixture B to room temperature, adding 0.5-2 parts of thermal initiator, and mixing to obtain the UV cationic delayed curing adhesive; during mixing, stirring and passing cooling water at a constant temperature of 20-30° C., and controlling the stirring speed to 30-40 rpm to reduce heat generation.
[0027] Specifically, the preparation method of the UV cationic delayed curing adhesive comprises the following steps:
[0028] (1) adding the aliphatic epoxy resin, alicyclic epoxy resin, epoxy toughening agent, oxetane, and epoxy diluent into a blending kettle, stirring at room temperature for 30 minutes to obtain a mixture;
[0029] (2) adding the synthesized cationic photoinitiator and silicon dioxide into a blending kettle, stirring and mixing at room temperature for 30 minutes to obtain a mixture;
[0030] (3) Cooling water is passed through to control the mixing temperature below 30° C., the thermal initiator BPO is added into the blending kettle, and the mixture is stirred for 10 minutes to obtain the UV cationic delayed curing adhesive.
[0031] Furthermore, in the step (1), the mixing and stirring speed is 500-1000 rad / min.
[0032] Furthermore, in the step (2), the mixing and stirring speed is 500-1000 rad / min.
[0033] Furthermore, in the step (3), the mixing and stirring speed is 100-200 rad / min, and the mixing and stirring is stopped after 30 minutes before packaging.
[0034] The present invention also provides the application of the UV cationic delayed curing adhesive in the field of electronic and electrical materials, specifically the application of bonding non-transparent substrates.
[0035] The technical solution of the present invention has the following advantages over the prior art:
[0036] (1) A liquid, single-component, medium-viscosity, thixotropic UV cationic delayed curing adhesive is used for delayed curing bonding of opaque substrates: LED365 or LED405 is used for curing, and the curing energy is 4000mJ / cm 2 , the open time is greater than 5 minutes, and the open time can be adjusted according to the UV light energy and the thickness of the glue coating, so that the separation of the glue coating, lighting, laminating and curing process can be realized. The glue has a certain reaction induction period. There is no obvious curing gel during the open time of the reaction induction period. After the reaction induction period, with the assistance of BPO, the glue quickly gels and solidifies, and the bonding strength greater than 1Mpa is generated 30 minutes after the substrate is laminated, which meets the requirements of bonding positioning. Subsequently, the dark reaction of cationic polymerization is used for post-curing or heating to accelerate curing to achieve the best bonding effect. The present invention can solve the problem that the curing depth of the colored UV glue system is poor, and the opaque substrate cannot be cured by the traditional UV glue curing process.
[0037] (2) The method for preparing a UV cationic delayed curing adhesive in the present invention has a simple process, is environmentally friendly, and has broad application prospects in the electronic and electrical industry. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0039] Example 1
[0040] 20g of bisphenol A epoxy resin YD-172, 10g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl) adipate, 15g of MX-154, 25g of 3-ethyl-3-hydroxymethyloxybutane, and 5g of carbon dodecadecyl glycidyl ether are added to a blending kettle in sequence, and stirred at room temperature for 30min at a stirring speed of 500r / min to obtain a mixture; then 2.5g of cationic photoinitiator UVI-6976 and 4 parts of silica TS720 are added, and stirred at room temperature for 30min at a stirring speed of 800r / min to obtain a mixture; finally, 0.8g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0041] Example 2
[0042] 10g of bisphenol A epoxy resin YD-172, 20g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl) adipate, 20g of MX-154, 20g of 3-methyl-3-hydroxymethyloxybutane, and 10g of butyl glycidyl ether are sequentially added into a blending kettle, stirred at a stirring speed of 500r / min for 30min at room temperature to obtain a mixture; then 2.0g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at a stirring speed of 800r / min for 30min at room temperature to obtain a mixture; finally, 1.5g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0043] Example 3
[0044] 20g of bisphenol A epoxy resin YD-172, 10g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl)adipate, 15g of BP3600, 20g of 3-ethyl-3-[[(2-ethylhexyl)oxy]methyl]oxetane, and 10g of butyl glycidyl ether are sequentially added into a blending kettle, stirred at a stirring speed of 500r / min for 30min at room temperature to obtain a mixture; then 3.0g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at a stirring speed of 800r / min for 30min at room temperature to obtain a mixture; finally, 0.5g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0045] Example 4
[0046] 15g of bisphenol A epoxy resin YD-172, 15g of polyurethane modified epoxy resin, 10g of bis((3,4-epoxycyclohexyl)methyl) adipate, 15g of BP3600, 25g of 3-ethyl-3-hydroxymethyloxybutane, and 5g of butyl glycidyl ether are sequentially added into a blending kettle, stirred at a stirring speed of 500r / min for 30min at room temperature to obtain a mixture; then 3.0g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at a stirring speed of 800r / min for 30min at room temperature to obtain a mixture; finally, 1.0g of 40% by mass BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0047] Example 5
[0048] 20g of bisphenol A epoxy resin YD-172, 10g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl)adipate, 20g of BP3600, 20g of 3-ethyl-3-[[(2-ethylhexyl)oxy]methyl]oxetane, and 8g of butyl glycidyl ether are sequentially added into a blending kettle, stirred at room temperature for 30min at a stirring speed of 500r / min to obtain a mixture; then 2.8g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at room temperature for 30min at a stirring speed of 800r / min to obtain a mixture; finally, 1.5g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0049] Comparative Example 1
[0050] 20g of bisphenol A epoxy resin YD-172, 10g of polyether modified epoxy resin EP4000, different weights of bis((3,4-epoxycyclohexyl)methyl) adipate, 15g of MX-154, 25g of 3-ethyl-3-hydroxymethyloxybutane, and 5g of carbon dodecadecyl glycidyl ether are added to a blending kettle in sequence, and stirred at room temperature for 30 minutes at a stirring speed of 500r / min to obtain a mixture; then 2.5g of cationic photoinitiator UVI-6976 and 4 parts of silica TS720 are added, and stirred at room temperature for 30 minutes at a stirring speed of 800r / min to obtain a mixture; finally, 0.8g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10 minutes to obtain the UV cationic delayed curing adhesive.
[0051] Comparative Example 1 did not add alicyclic epoxy resin, had a longer open time, and a slower increase in strength. When the film thickness was 300 microns or less, the shear strength of 1 MPa could not be reached in 30 minutes.
[0052] Comparative Example 2
[0053] 10g of bisphenol A epoxy resin YD-172, 20g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl) adipate, 20g of MX-154, and 30g of 3-methyl-3-hydroxymethyloxybutane are sequentially added into a blending kettle, stirred at a stirring speed of 500r / min for 30min at room temperature to obtain a mixture; then 2.0g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at a stirring speed of 800r / min for 30min at room temperature to obtain a mixture; finally, 0.5g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed curing adhesive.
[0054] In Comparative Example 2, all diluent monomers are oxetane (which reacts faster after the induction period), the open time is short, less than 5 minutes, and the strength can reach 1 MPa in 30 minutes.
[0055] Comparative Example 3
[0056] 10g of bisphenol A epoxy resin YD-172, 20g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl)adipate, 20g of MX-154, and 30g of butyl glycidyl ether are sequentially added into a blending kettle, stirred at room temperature for 30min at a stirring speed of 500r / min to obtain a mixture; then 2.0g of cationic photoinitiator UVI-6976 and 4.0 parts of silica TS720 are added, stirred at room temperature for 30min at a stirring speed of 800r / min to obtain a mixture; finally, 0.5g of 40% mass fraction of BPO is added, and the mixture is stirred and mixed at a stirring speed of 100r / min for 10min to obtain the UV cationic delayed glue.
[0057] In Comparative Example 3, all diluent monomers were glycidyl ether, the open time was too long, the film thickness was 300 microns or less, and the strength after 30 minutes did not reach 1 MPa.
[0058] Comparative Example 4
[0059] 20g of bisphenol A epoxy resin YD-172, 10g of polyether modified epoxy resin EP4000, 10g of bis((3,4-epoxycyclohexyl)methyl) adipate, 15g of MX-154, 25g of 3-ethyl-3-hydroxymethyloxybutane, and 5g of carbonyl glycidyl ether are added to a blending kettle in sequence, and stirred at room temperature for 30min at a stirring speed of 500r / min to obtain a mixture; then 2.5g of cationic photoinitiator UVI-6976 and 4 parts of silica TS720 are added, and the mixture is stirred at room temperature for 30min at a stirring speed of 800r / min to obtain the UV cationic delayed curing adhesive.
[0060] In Comparative Example 4, no thermal initiator was added, the open time was too long, the strength increased slowly, the film thickness was 300 microns or less, and the strength reached 1 MPa in 30 minutes.
[0061] Effect evaluation 1
[0062] (1) UV cationic delayed curing adhesive was applied to the stainless steel substrate with different adhesive thicknesses. 2 After being exposed to light of different energy levels, the colloid was placed for different periods of time, and the time when the colloid obviously increased in viscosity was recorded as the open time.
[0063] Table 1 Open time of different glue coating thickness (s)
[0064]
[0065] (2) UV cationic delayed curing adhesive was applied to the stainless steel substrate with different adhesive thicknesses. 2 After being exposed to energy light for 120 seconds, the panels were bonded together, and the shear strength on stainless steel was tested after curing at room temperature for 30 minutes.
[0066] Table 2 Comparison of shear strength of stainless steel with different adhesive thickness after 30 minutes of bonding (Mpa)
[0067]
[0068] (3) UV cationic delayed curing adhesive coating thickness 200μm, 4000mj / cm 2 After being exposed to energy light for 120 seconds, the panels were bonded together to test the shear strength of stainless steel at different curing times at room temperature.
[0069] Table 3 Shear strength of stainless steel after curing at room temperature for different times after bonding (Mpa)
[0070]
[0071] (4) UV cationic delayed curing adhesive was applied to the stainless steel substrate at different thicknesses and at 4000 mj / cm2 After being exposed to energy light for 120 seconds, the panels were bonded together and the shear strength of the panels cured at room temperature for 24 hours on stainless steel was tested.
[0072] Table 4 Shear strength of stainless steel after bonding at different adhesive thicknesses and curing at room temperature for 24 hours (Mpa)
[0073]
[0074] (5) UV cationic delayed curing adhesive was coated on a stainless steel substrate with a thickness of 200 μm and a curing rate of 4000 mj / cm 2 After being exposed to energy light for 120 seconds, the panels were bonded together, and the shear strength of the panels on different substrates was tested after curing at room temperature for 30 minutes and 24 hours.
[0075] Table 5 Shear strength of different substrates after curing at room temperature for 30 minutes and 24 hours (Mpa)
[0076]
[0077] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A UV cationic delayed curing adhesive, characterized in that: By weight, it includes the following components:
2. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The aliphatic epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and modified epoxy resin; the modified epoxy resin is selected from polyurethane modified epoxy resin or polyether modified epoxy resin.
3. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The alicyclic epoxy resin is selected from one or more of bis((3,4-epoxycyclohexyl)methyl)adipate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate, 4-vinyl-1-cyclohexene diepoxide and 3,4,3',4'-diepoxydicyclohexane.
4. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The epoxy toughening agent is selected from epoxidized butadiene or polyurethane toughening agents.
5. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The oxetane is selected from one or more of 3-methyl-3-hydroxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-[[(2-ethylhexyl)oxy]methyl]oxetane, 3-ethyl-3-((oxiranylmethoxy)methyl)oxetane and 3,3'-(oxybismethylene)bis(3-ethyl)oxetane.
6. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The epoxy diluent is selected from one or more of butyl glycidyl ether, dodecanediol glycidyl ether, 1,4-hexanediol diglycidyl ether and 1,6-hexanediol diglycidyl ether.
7. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The cationic photoinitiator is selected from one or more of 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluorophosphate, (4-octyloxyphenyl)phenyliodonium hexafluoroantimonate, a triarylsulfonium salt mixed initiator and a triarylsulfonium salt mixed initiator.
8. The UV cationic delayed curing adhesive according to claim 1, characterized in that: The thermal initiator is dibenzoyl peroxide.
9. A method for preparing the UV cationic delayed curing adhesive according to any one of claims 1 to 8, characterized in that: The steps include: (1) mixing 20-30 parts of aliphatic epoxy resin, 5-10 parts of alicyclic epoxy resin, 15-20 parts of epoxy toughening agent, 20-30 parts of oxetane, and 5-10 parts of epoxy diluent by weight to obtain a mixture A; (2) further mixing the mixture A with 2-5 parts of a cationic photoinitiator and 2-5 parts of silicon dioxide to obtain a mixture B; (3) Cooling the mixture B to room temperature, adding 0.5-2 parts of thermal initiator, and mixing to obtain the UV cationic delayed curing adhesive; during mixing, stirring and passing cooling water at a constant temperature of 20-30° C., and controlling the stirring speed to 30-40 rpm to reduce heat generation.
10. Use of the UV cationic delayed curing adhesive according to any one of claims 1 to 8 in the field of electronic and electrical materials.
Citation Information
Patent Citations
Quinoline derivatives, processes for their preparation, their use, pharmaceutical compositions containing them and a method for the preparation of these pharmaceutical compositions
EP0030044A1
Influence probing arrangement and method for its realization
EP0030056A1
Apparatus for continuous and direct measurement of the sea surface temperature
EP0040059A2